A triad of shoulder injuries following cardioversion: a case report - Tan, Eng Kee; Ahmad Hanif, Khairil Anwar; Seri Masran, Siti Munira; Che Hamzah, Fahrudin (Springer Science and Business Media LLC, 2024)
Transthoracic defibrillation and cardioversion are commonly used techniques to resuscitate a patient during acute cardiac arrhythmic events. There are numerous complications associated with these procedures. We report a previously unreported complication where a patient suffered from a supraspinatus tear after cardioversion for ventricular tachycardia. There are numerous complications associated with these procedures. We report a previously unreported complication where a middle-aged Chinese patient with no previous trauma history suffered from a supraspinatus tear after cardioversion for ventricular tachycardia.